2012
DOI: 10.3762/bjoc.8.29
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of oleophilic electron-rich phenylhydrazines

Abstract: SummaryPhenylhydrazines 1 substituted with two or three long-chain alkyl, alkoxy or alkylsulfanyl groups were successfully prepared by acid-induced removal of the Boc group in hydrazides 2. The reaction is carried out with 5 equivalents of TfOH in CF3CH2OH/CH2Cl2 at −40 °C for 1.5 min. Under these conditions, the deprotected hydrazine 1 is fully protonated, which increases its stability in the reaction medium. The hydrazines were isolated in 60–86% yields and purities >90%. The hydrazides 2 were obtained in 43… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…Magnetic studies of 1 [10]d at 500 Oe revealed nearly ideal paramagnetic behavior in both the liquid crystalline and isotropic phases. Similar to previous observations for 1 [8]a, no abrupt changes were detected upon phase transitions, which indicates that the spins are isolated in both phases. 2 In contrast, a sample of 1 [8]b showed a small decrease of magnetization upon isotropic to mesophase transition.…”
Section: Magnetic and Photovoltaic Characterizationsupporting
confidence: 90%
See 1 more Smart Citation
“…Magnetic studies of 1 [10]d at 500 Oe revealed nearly ideal paramagnetic behavior in both the liquid crystalline and isotropic phases. Similar to previous observations for 1 [8]a, no abrupt changes were detected upon phase transitions, which indicates that the spins are isolated in both phases. 2 In contrast, a sample of 1 [8]b showed a small decrease of magnetization upon isotropic to mesophase transition.…”
Section: Magnetic and Photovoltaic Characterizationsupporting
confidence: 90%
“…Similar to previous observations for 1 [8]a, no abrupt changes were detected upon phase transitions, which indicates that the spins are isolated in both phases. 2 In contrast, a sample of 1 [8]b showed a small decrease of magnetization upon isotropic to mesophase transition. 3 Time-of-Flight (ToF) studies of an unaligned sample of 1 [10]d in cells of 12.5 mm or 4.75 mm gap (applied voltage of 30-50 kV cm À1 ) showed only a negligible transient photocurrent in the range of 80-30 C that was insufficient to calculate charge mobility.…”
Section: Magnetic and Photovoltaic Characterizationsupporting
confidence: 90%
“…Lithiation of 7* with tBuLi and reaction with di-tert-butyl azodicarboxylate (DTBAD) gave the protected hydrazine 8*, which was deprotected with trifluoromethanesulfonic acid (TfOH) to give the crude hydrazine 2*, according to a general procedure. [17] The bromide 7* was obtained by alkylation of 5-bromopyrogallol with tosylate 9*, which, in turn, was obtained from (S)-3,7-dimethyloctanol (ee >98%).…”
Section: Synthesismentioning
confidence: 99%
“…To a solution of carbamoyl chloride 5b or 5c [12] (0.5 mmol) in dry benzene (15 mL), a solution of freshly prepared 3,4,5-trioctyloxyphenylhydrazine [17] (2) or 3,4,5-tris((S)-3,7-dimethyloctyloxy)phenylhydrazine (2*, 0.6 mmol) and Et 3 N (0.65 mmol) in dry benzene (5 mL) was added. The mixture was stirred for 2 h at 50°C…”
Section: General Procedures For 6-oxoverdazylsmentioning
confidence: 99%
See 1 more Smart Citation